Exercício físico e menopausa - Zanesco, Angelina [UNESP]; Zaros, Pedro Renato [UNESP] (My University, 2009)
It is believed that estrogen deficiency, lipid profile alterations, body weight gain, and sedentary lifestyle are strongly associated with the increased incidence of arterial hypertension in postmenopausal women. In an attempting to reduce the incidence of arterial hypertension in this population, a variety of approaches has been used, but the results are conflicting and the changing in lifestyle has been proposed and an important preventive action to control the arterial hypertension and associated risk factors in this women age - mainly practice of physical exercise. Continuous exercise has been used as an important approach in management cardiovascular disease and endocrine-metabolic disorders. Continuous exercise prescription is characterized by, at least, 30 minutes of moderate-intensity physical activity (60 to 70% of maximum heart rate), three days of the week. Intermittent exercise is characterized by low intensity exercise periods, alternating with high-intensity exercise periods, ranging of 50 to 85% of the maximum heart rate, during ten minutes. Intermittent exercise has been employed as training program in weight loss therapy and personal training because previous studies have shown similar metabolic adaptations and aerobic capacity after continuous or intermittent exercise. This review focused on the relevance of continuous and intermittent exercise on the blood pressure control, discussion of the data found in experimental model of menopause and in women and the relationship between incidence of arterial hypertension and its genesis in postmenopausal women.
Physical exercise and menopause
Keywords: Exercise; Hypertension; Menopause; Motor activity; Women